Determination of Odorants in Varietal Wines from International Grape Cultivars (Vitis vinífera) Grown in NW Spain - Vilanova, M.; Genisheva, Z.; Graña, M.; Oliveira, J.M. (South African Journal of Enology and Viticulture, 2016)
This work was carried out to investigate the odorants found in ten varietal wines from different international grape cultivars (Merlot, Cabernet Sauvignon, Pinot noir, Tempranillo, Sauvignon blanc, Riesling, Chardonnay, Pinot gris, Pinot blanc and Gewürztraminer) grown in northwest Spain. Monoterpenes, alcohols, fatty acids, ethyl esters, acetates and volatile phenols were determined by gas chromatographymass spectrometry (GC-MS). The results showed that Gewürztraminer white wines had the highest concentration of volatile compounds (35.7 mg/L). Monoterpenes, linalool, terpineol, citronellol and nerol were detected only in Riesling and Gewürztraminer white wines. In the red wines, Cabernet Sauvignon followed by Merlot wines showed the highest concentration of total volatile composition (55.60 mg/L and 50.90 mg/L respectively), characterised by a higher concentration of alcohols. Based on the individual odour threshold, white Gewürztraminer and red Pinot noir wines showed the highest total OAV value. ANOVA has shown significant differences among wines. Principal component analysis performed a grouping of the monovarietal wines – Sauvignon blanc-Pinot blanc-Riesling and Pinot gris gris-Gewürztraminer in the white wines, and Cabernet Sauvignon-Tempranillo in the red wines.